2021
DOI: 10.2196/29251
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Attitudes Toward Telemedicine Consultations During the COVID-19 Pandemic: Cross-sectional Study

Abstract: Background To mitigate the effect of the COVID-19 pandemic, health care systems worldwide have implemented telemedicine technologies to respond to the growing need for health care services during these unprecedented times. In the United Arab Emirates, video and audio consultations have been implemented to deliver health services during the pandemic. Objective This study aimed to evaluate whether differences exist in physicians’ attitudes and perceptions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 56 publications
0
44
0
2
Order By: Relevance
“…11,12 The natural experiment of telehealth use during COVID-19 has created opportunities to learn from new experiences, 13,14 and there has been emerging research exploring telehealth in primary care. [15][16][17][18] As this research progresses, an in-depth understanding of GP perceptions regarding telehealth remains limited in the Australian setting. This study investigated GP perceptions on providing telehealth (telephone and videoconsultations) services in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The natural experiment of telehealth use during COVID-19 has created opportunities to learn from new experiences, 13,14 and there has been emerging research exploring telehealth in primary care. [15][16][17][18] As this research progresses, an in-depth understanding of GP perceptions regarding telehealth remains limited in the Australian setting. This study investigated GP perceptions on providing telehealth (telephone and videoconsultations) services in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…However, a high chance of misdiagnosis due to lack of physical examination and less personal rapport with patients were the disadvantages perceived by the physicians. Furthermore, the physicians were more confident in delivering care with combined audio-video care than with audio care alone [ 38 ]. Another study that assessed perceived advantages and disadvantages among Saudi physicians in the Taif region showed that almost a third of the participants believed that telemedicine increased the effectiveness of therapeutic intervention and 44% perceived that virtual care improved patient care.…”
Section: Discussionmentioning
confidence: 99%
“…While the implication of telemedicine mobile applications still faces certain challenges and barriers [ 23 26 ], adoption of these technologies has been on the rise [ 9 ]. Our sister study has previously reported on physician’s attitude and confidence towards telemedicine in treating acute conditions, providing patients with health education and enhancing the patient-physician rapport [ 27 ]. This study on the other hand, aimed to explore the impact of using a mobile application to manage and attend patient-physician consultations on the overall satisfaction of the patients using telemedicine in Abu Dhabi.…”
Section: Introductionmentioning
confidence: 99%